GENETIC VARIABILITY AMONG GENOTYPES AND CHARACTER ASSOCIATION IN TION IN TION IN KHARIF POTATO (SOLANUM TUBEROSUM L.) FOR DIFFERENT TRAITS FOR DIFFERENT TRAITS - MAHARANA, JYOTSHNARANI; AND PRAVEEN JAKHAR, C. M. PANDA (The Bioscan, 2018)
A study was conducted during kharif season of 2014 and 2015 to estimate the genetic variability, heritability, genetic advance and correlation among 16 genotypes of potato (Solanum tuberosum L.) under rainfed conditions. Potato genotypes were evaluated for different growth parameters, yield attributes and yield characters. Statistical analysis for days to 50% flowering indicated significant variation among tested genotypes and Kufri Badshah recorded maximum value (43 days). Maximum number of tubers/plant were recorded in Kufri Ashok (7.81), which was statistically at par with genotypes Kufri Lalima, Kufri Pukhraj and Kufri Lalit. In terms of marketable yield, Kufri Pukhraj gave maximum yield of 107.4q/ha which was closely followed by Kufri Jyoti (107.3q/ha). Out of 18 parameters, eight parameters showed heritability >90%. High heritability coupled with high genetic advance was observed for leaflets/plant, leaf area, total tuber yield and marketable yield. Marketable yield had positive significant correlation with all the parameters except for plant height at 30 days after planting and tuber length width ratio. The high phenotypic and genotypic correlation was obtained for tubers/plant (0.953 and 0.922), total tuber yield (0.935 and 0.922). The study showed sufficient genetic variability among genotypes which can be exploited in future breeding programmes which would be effective in boosting kharif potato cultivation in Koraput region of Odisha.